Function of Simile Style in 'Teruslah Bodoh Jangan Pintar' Novel by Tere Liye and Lesson Plan - Aclin Choirin Nisa; Hermandra; Charlina (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
The purpose of this study was to explore: 1) the function of using simile language style in the novel Teruslah Bodoh Jangan Pintar by Tere Liye; 2) the lesson plan for learning using a dual strategy through the Google form file upload option in class XII of high school. This library research uses a qualitative descriptive method. The subject of the study was the novel Teruslah Bodoh Jangan Pintar by Tere Liye. Documentation techniques were used to obtain research data from written sources. Data were analyzed using the Miles and Huberman method of data analysis, which includes data reduction techniques, data presentation techniques, and conclusion drawing techniques. The results of the study: 1) simile functions as an effective rhetorical tool to describe various emotional, social, and environmental aspects in the narrative. Through the 15 simile quotes analyzed, the author effectively conveys profound messages about past trauma, social injustice, and hopes for peace, as well as criticizing environmental exploitation. This study will provide further insight into how simile language style can create complex meanings in literary works in the future. In addition, this study also supports Indonesian language learning in high school by providing learning media in the form of concrete examples of language style analysis that are relevant to learning outcomes and reading and viewing elements; 2) the lesson plan for learning smile language style in the novel Teruslah Bodoh Jangan Pintar by Tere Liye contains 20 core activities involving a process skills approach, copying assigment techniques, and test techniques using the Google form media with the file upload option.